2006
DOI: 10.1590/s0104-11692006000300002
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing nursing staff members' participation in continuing education

Abstract: .Given the importance of continuing education to improve nursing practice, research has been done to study the phenomenon of nursing staff members' participation and to try and explain the reasons that motivate individuals to take part in continuing education activities. Results have found that motivational orientations of nursing staff are the main force to start participatory behavior, which can also be positively and/or negative influenced by demographic variables, life situation and the structure of the ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 11 publications
(9 reference statements)
1
15
1
5
Order By: Relevance
“…This result disagrees with several results, which indicated that motivation is one of the main factors affecting the employees' participation in training programs. [10,28,29] Limitations For this study, there was no previous published educational need assessment for nurses in El-Gharbia Government or in Egypt and these reduced the number of article included in this review on the national level.…”
Section: Discussionmentioning
confidence: 97%
“…This result disagrees with several results, which indicated that motivation is one of the main factors affecting the employees' participation in training programs. [10,28,29] Limitations For this study, there was no previous published educational need assessment for nurses in El-Gharbia Government or in Egypt and these reduced the number of article included in this review on the national level.…”
Section: Discussionmentioning
confidence: 97%
“…This difference was significant between the pre and post (p<0.001) periods, and between the pre-training and six-months-later periods (p<0.001), as shown in Figure 2. techniques, and attitudes learned in a training course, the stronger their participation (7) .…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…Pour agir avec compétence, ces professionnels doivent intervenir en se fondant sur des normes de pratique et des résultats probants [1] . La formation continue (FC) est dès lors un moyen indispensable pour favoriser l'actualisation des connaissances, le maintien des standards de pratique ainsi que le déve-loppement des compétences [2][3][4][5] . La FC se définit comme étant un processus d'apprentissage continu, planifié pour améliorer les connaissances, les attitudes et les habiletés des infirmiers(ères) et elle est mise en oeuvre, notamment, à partir des besoins exprimés [3] .…”
Section: Introductionunclassified
“…Des écrits en pédagogie, en méde-cine et en sciences infirmières relèvent que certaines méthodes d'enseignement sont efficaces en FC, principalement celles qui recourent à une approche participative [3,7,14] . La recension des écrits et nos expériences cliniques indiquent que la FC en traumatologie s'avère essentielle [5,6] , que les collègues de la discipline la réclament et qu'elle doit reposer sur les besoins exprimés [3,4,15] .…”
Section: Introductionunclassified